Hypoglycemia Induced by Insulin as a Triggering Factor of Cognitive Deficit in Diabetic Children - Vanessa Rodrigues Vilela; Any de Castro Ruiz Marques; Christiano Rodrigues Schamber; Roberto Barbosa Bazotte (The Scientific World Journal)
This paper provides an overview of insulin-induced hypoglycemia as a triggering factor of cognitive deficit in children with type 1 diabetes mellitus. For this purpose, databases from 1961 to 2013 were used with the objective of detecting the primary publications that address the impact of hypoglycemia on cognitive performance of diabetic children. The results obtained from experimental animals were excluded. The majority of studies demonstrated that the cognitive deficit in diabetic children involves multiple factors including duration, intensity, severity, and frequency of hypoglycemia episodes. Additionally, age at the onset of type 1 diabetes also influences the cognitive performance, considering that early inception of the disease is a predisposing factor for severe hypoglycemia. Furthermore, the results suggest that there is a strong correlation between brain damage caused by hypoglycemia and cognitive deterioration. Therefore, a more cautious follow-up and education are needed to impede and treat hypoglycemia in children with diabetes mellitus.